The Administration Guidelines among the Digital Age Education Internal Quality Assurance of School under Nakhon Sawan Primary Educational Service Area Office 1 - Moungson, Jeraporn; Suntawan, Teeppipat; Tawee, Supphachai (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
The objectives of this research were to: 1) study the problems of internal quality assurance management of schools, 2) find the guidelines of internal quality assurance management of schools in the digital age and 3) evaluate guidelines of internal quality assurance management. The conducting research according to research and development procedures.: Step 1, study the problems of internal quality assurance management of schools. The sample group consisted of 317 people from school administrators and teachers were selected by stratified random sampling. The research instrument was a questionnaire. The statistics used for data analysis were mean and standard deviation. Step 2, find the guidelines of internal quality assurance management of schools in the digital age. The samples were 7 experts in a focus group discussion. The statistics used for data analysis was content analysis. And step 3, evaluate guidelines of internal quality assurance management of schools. The samples were 5 school administrators. The research instrument was the quality assessment form and the statistics used for data analysis were mean and standard deviation. The results of the research were as follows: 1) The problems of internal quality assurance management of schools in the digital age was at a high level (x = 4.17, S.D. = 0.41) 2) Guidelines of internal quality assurance management of schools in the digital age was school administrators in schools have clearly appointed, who involved with implementation of quality assurance. Base on participation and support personnel to use appropriate and diverse digital technology. Including, monitoring of each step regularly and analyze operating results in order to continuous improvement and development, and 3) Evaluate guidelines of internal quality assurance management of schools in the digita l age was highest level in every aspect. The aspect with the highest averages were feasibility ( x = 4.64, S.D. = 0.57), propriety ( x = 4.63, S.D. = 0.55), accuracy ( x = 4.59, S.D. = 0.57) and utility ( x = 4.53, S.D. = 0.55), respectively.